2019
DOI: 10.1371/journal.pone.0216215
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of retinal hypoxia and photoreceptor degeneration in patients with age-related macular degeneration

Abstract: Although drusen have long been acknowledged as a primary hallmark of dry age-related macular degeneration (AMD) their role in the disease remains unclear. We hypothesize that drusen accumulation increases the barrier to metabolite transport ultimately resulting in photoreceptor cell death. To investigate this hypothesis, a computational model was developed to evaluate steady-state oxygen distribution in the retina. Optical coherence tomography images from fifteen AMD patients and six control subjects were segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Emerging data has shed light on extra-mitochondrial sources of ROS specifically in the outer retina and even in the outer segment of photoreceptors [52,53]. It was previously shown that oxygen is mainly absorbed at the level of the photoreceptors [54] and thus this site is most prone to oxidative stress, both in physiology and pathology [55]. To build on that, it seems that blue light exposure on outer segment discs as well as ectopic oxidative phosphorylation in the outer segment both pose a greater need for effective free radical scavengers in the outer segment-RPE interface [56][57][58].…”
Section: Serine Is An Anti-oxidant and Mediator Of Inflammationmentioning
confidence: 99%
“…Emerging data has shed light on extra-mitochondrial sources of ROS specifically in the outer retina and even in the outer segment of photoreceptors [52,53]. It was previously shown that oxygen is mainly absorbed at the level of the photoreceptors [54] and thus this site is most prone to oxidative stress, both in physiology and pathology [55]. To build on that, it seems that blue light exposure on outer segment discs as well as ectopic oxidative phosphorylation in the outer segment both pose a greater need for effective free radical scavengers in the outer segment-RPE interface [56][57][58].…”
Section: Serine Is An Anti-oxidant and Mediator Of Inflammationmentioning
confidence: 99%
“…Recent evidence suggests that mild, but chronic hypoxic conditions, that may develop due to reduced choroidal blood flow and volume 5 7 , choroidal ischemia 8 , and accumulation of drusen may also be important for the development and progression of the non-exudative form of AMD 8 . The involvement of hypoxia in disease is further supported by recent computational models showing a strong correlation between hypoxia and retinal thinning during AMD development 9 .…”
Section: Introductionmentioning
confidence: 69%
“…Drusen material accumulating between the RPE and the Bruch's membrane diminish the oxygen supply from the choroid to the retina (96). RPE cells suffering from hypoxia can result in the release of vascular endothelial growth factor (VEGF) already prior to the production of inflammatory markers (97).…”
Section: Potential Of Mdscs In Provoking Angiogenesis In Diseased Retinamentioning
confidence: 99%